Boy with a Violin : A Story of Survival - Fein, Yochanan (Book collections on Project MUSE., 2022)
Boy with a Violin recounts the compelling story of child violin prodigy Yochanan Fein--from his miraculous survival in the Kaunas Ghetto through his daring escape from Soviet Lithuania to Poland, before immigrating to Israeli in 1950.